Increased carotid intima‐media thickness in African American pediatric kidney transplant recipients. (8th February 2018) - Sgambat, Kristen; Clauss, Sarah; Lei, K. Y.; Song, Jiuzhou; Rahaman, Shaik O.; Lasota, Margaret; Moudgil, Asha
Abstract: Early signs of subclinical CV dysfunction can be detected by ultrasound for CIMT. Although A‐A are at high risk for CV disease, CIMT of A‐A kidney transplant recipients has not been previously investigated. The aim of this prospective, controlled, longitudinal study was to investigate determinants of CIMT in a multiracial pediatric kidney transplant population, with a focus on A‐A. Transplant recipients (n = 42) had BMI, waist‐to‐height ratio, fasting glucose, lipid panel, HbA1c%, and CIMT measured at 1, 18, and 30 months post‐transplant. Twenty‐four healthy children (14 A‐A) served as controls. CIMT of A‐A transplant (0.49, 0.49, and 0.48 mm) was higher than non‐AA transplant (0.43, 0.44, and 0.44 mm) at 1, 18, and 30 months and higher than A‐A controls (0.47 mm). Hyperparathyroidism prior to transplant predicted high CIMT‐for‐race. A‐A race was associated with 10% higher CIMT vs non‐A‐A transplant. Metabolic syndrome was associated with 0.03 ± 0.01 mm increase in CIMT among A‐A transplant recipients only. In conclusion, A‐A kidney transplant recipients have increased CIMT. Metabolic syndrome disproportionately affects CIMT of A‐A children post‐transplant. Identification of subclinical CV damage, detected by CIMT, may provide an opportunity for early detection of CV risk in this vulnerable population.